Optimal Power Flow Through Variable Frequency Transformer Using Different Optimization Techniques - Sheikh, Aabid Hussain; Bakhsh, Farhad Ilahi (Distributed Generation & Alternative Energy Journal, 2022)
For synchronous and asynchronous connectivity of separate power grids, phase shifting transformers (PST), the high-voltage-direct-current (HVDC) converters and variable-frequency-transformer (VFT) are viable options. Natural damping and high overloading capabilities are inherent in the VFT, which is critical for power grid reliability and stability. This article reports the optimal power flow across a power system involving the implementation of several meta-heuristic optimization techniques based control strategy. Several optimization techniques are applied to optimize the gains of proportional-integral-derivative (PID) controller which aids in regulating the system dynamic response. The firefly algorithm based PID controller performs better in contrast to other optimization techniques in improving the system dynamics. The DC motor accustomed with PID controller provides the required torque necessary for power transfer between two connected grids. Sensitivity analysis is exhibited to inspect the strength of developed power system against deviations in certain system parameters. A separate study is done for the asynchronous operation of VFT based power system using firefly algorithm with different DC motor torque. To validate the effect of VFT over HVDC total harmonic distortion analysis has been carried out to check for the harmonic content in the rotor and stator current of VFT.